Development and evaluation of reading materials for promoting public understanding of environmental issues in the Philippines - Rabago, Lilia Malabonga 1933-
This study is an attempt to bring the findings of scientific researches in environmental science to their intended beneficiaries, the general public. The work has two phases: DEVELOPMENT (phase 1) and EVALUATION (Phase 2) of reading materials (booklets) on three environmental issues -- deforestation, marine pollution and wildlife depletion.